Spatial heterogeneity of polycyclic aromatic hydrocarbons pollution in surface soil of China and its response to regional energy consumption - Chen, Kun; Shen, He; Zang, Shuying; Sun, Li (Frontiers in Environmental Science, 2024)
The regional variation of energy structure in China is a significant contributor to the geographic distribution of polycyclic aromatic hydrocarbons (PAHs) in soils, posing a substantial risk to food safety and human health. However, the precise mechanisms and extent to which energy consumption influences the spatial variability of PAHs remain largely unknown. To address this research gap, PAHs data in surface soils across China screened from 155 literatures between 2003 and 2022, coupled with anthropogenic indicators were used to investigate the concentrations, sources, and spatial heterogeneity of the effects of energy consumption on PAHs. Total PAH concentrations exhibited a range of four orders of magnitude from 1.05 to 6,778 μg kg−1, indicating weak to heavy contamination and exhibiting strong spatial variability influenced by human factors. Furthermore, 3–4-ring PAHs were dominant, accounting for an average of 25.07% and 38.55%, respectively, reflecting the significant role of coal in China energy consumption and the associated coal-smoke pollution as a primary factor in ecological environment destruction. The spatial distributions of mean total PAH concentrations descended in the order of Northeast China > North China > Central China > East China > Northwest China > Southwest China > South China, with different PAH composition profiles among regions affected by energy consumption. The geographical weighted regression (GWR) model was used to explore the spatial heterogeneity of energy factors affecting on PAH concentrations. Natural gas, oil, and coal were identified as energy sources with a significant positive correlation to PAH pollution. This indicated that combustion and traffic sources were the primary contributors to PAHs in surface soil in China, with coal, natural gas combustion, and oil consumption identified as the principal energy factors influencing PAH concentrations. The results of this study provide a foundation for future efforts to prevent and control soil pollution.